Dietary intakes of flavan-3-ols and cardiovascular health: a field synopsis using evidence mapping of randomized trials and prospective cohort studies. - Raman, Gowri.; Shams-White, Marissa.; Avendano, Esther E.; Chen, Fan.; Novotny, Janet A.; Cassidy, Aedin. (2018)
Background: There is considerable interest in the impact of increased flavan-3-ol intake on cardiovascular disease (CVD) and diabetes outcomes. Through evidence mapping, we determined the extent of the evidence base to initiate a future systematic review investigating the impact of flavan-3-ol intake on CVD and diabetes outcomes.; Keywords: Cardiovascular disease, Diabetes, Lipids, Flavan-3-ols, Evidence mapping, Cocoa, Tea, Berries, Cinnamon, Red wine.; Springer Open.